Silver Diamine Fluoride in Clinical Pediatric Dentistry - Sarjana Mishra1 , Susant Mohanty2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Silver diamine fluoride is the most recent advancement in the field of dentistry. Its history dates back to the1960s and since its invention there was no looking back. People across the globe and different races andcultures have benefitted from SDF. With almost no adverse reactions, pocket-friendly, and highly effectivequalities in its stride, SDF has emerged as a powerful tool in caries prevention, especially in a countylike India where the oral health of a child is neglected. This review focuses on the history, indications,contraindications, mechanism, and safety margin of SDF as a dental material.